The Effect of Magnetic Field on Electrodeposition of Nickel; Investigation by Quartz Crystal Microbalance - CHIBA, Atsushi; HAMANO, Manabu; YOSHIHARA, Sachio; SATO, Eiichi (Hyōmen gijutsu, 1995)
A study of the effect of a magnetic field on the electrodeposition of nickel using a quartz crystal microbalance (QCM) showed that the efficiency of electrodeposition was decreased by the magnetic field, and that this decrease was effective at a cathode charge below 0.1C/cm2.